Analysis of collagen fibers in keratocystic odontogenic tumor and ameloblastoma: A polarizing microscopic study - Kalavani Peddapelli; Venkateswara Rao; Manchikatla Praveen Kumar; Taneeru Sravya; Dumpala Rakesh (Wolters Kluwer Medknow Publications, 2019)
Introduction: Collagen forms an integral part of connective tissue and maintains its structural integrity. It has natural birefringence which is attributed to the arrangement of its fibers and is enhanced by special stains such as picrosirius red through polarizing microscopy. The polarization colors differ according to the fiber thickness and pattern of arrangement which in turn related to aggressiveness. Hence, the present study was conducted to evaluate collagen fibers in keratocystic odontogenic tumor (KCOT) and ameloblastoma using polarizing microscopy. Aim: This study aims to compare and correlate different types and patterns of collagen fibers in KCOT and ameloblastoma using picrosirius red stain under polarizing microscopy to delineate their aggressiveness. Materials and Methods: The color, thickness, and orientation of collagen fibers in the KCOTs (n = 15) and ameloblastomas (n = 15) were studied histochemically by staining the sections with picrosirius red and examined under polarizing microscope using image analyzer software. Results: When collagen fiber bundles in KCOT and ameloblastoma were compared, significant difference was noted between yellowish-orange collagen fiber bundles, but no significant difference was observed between greenish-yellow and orange-red collagen bundles. With respect to orientation and organization, the results are statistically significant (P < 0.05). Conclusion: The connective tissue stroma of KCOT could be regarded not just as a structural support but as a functional part of the lesion. In KCOT, the thin, parallel, and loosely arranged greenish-yellow collagen fibers may be attributed to its high recurrence rate and biological aggressiveness.